Model Kolaborasi Bisnis Melalui Koperasi Pondok Pesantren Di Jawa Timur - Syauqi, Muhammad (Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
Partial research examines koperasi pondok pesantren (kopontren) with a specific emphasis on business collaboration between kopontren, particularly in East Java. Syirkah al inan represents a collaborative model involving two or more entities contributing capital and participating in management based on mutual agreements and the contributions of each participant. The case study method constitutes a qualitative research design that investigates real-life scenarios through the collection of comprehensive and indepth data from diverse sources, ultimately reporting the findings in a descriptive format that outlines the emergent themes. Capital collaboration for the development of kopontren within the Koperasi Sarekat Bisnis Pesantren (KSBP) organization is facilitated through member contributions via principal and voluntary savings, partnerships with Lembaga Pengelola Dana Bergulir Koperasi Usaha Mikro, Kecil dan Menengah (LPDB-KUMKM), and collaborations with Sharia banks. Second, product collaboration involves the exchange of goods through buying and selling activities either between kopontren or with suppliers. Third, network collaboration leverages Islamic boarding school alumni as a sales network for products. Fourth, human resources (HR) collaboration is characterized by the transfer of knowledge and skills among stakeholders and in cooperation with governmental entities. The utilization of business capital within KSBP is derived from Sharia banks, LPDB-KUMKM, as well as members’ principal savings, mandatory savings, and voluntary savings. The collaboration process engages KSBP members or KSBP alongside suppliers to fulfill the demand for goods, acknowledging that not all KSBP members possess the capability to produce goods. Network collaboration incorporates alumni from each Islamic boarding school as a sales network for products. Additionally, HR collaboration entails the exchange of knowledge and skills among constituents and in conjunction with governmental bodies.